2013
DOI: 10.5511/plantbiotechnology.13.0905b
|View full text |Cite
|
Sign up to set email alerts
|

ATL54, a ubiquitin ligase gene related to secondary cell wall formation, is transcriptionally regulated by MYB46

Abstract: We previously characterized Arabidopsis Tóxicos en Levadura54 (ATL54), a ubiquitin ligase associated with secondary cell wall formation. The ATL54 gene is co-expressed with secondary wall-associated genes, and the knock-out of ATL54 up-regulates the expression of cellulose, lignin, and xylan biosynthetic genes in apical stem portions of four-week-old plants. Here, we report the tissue-level localization patterns and the regulation of ATL54 expression. The β-glucuronidase (GUS) reporter gene driven by the ATL54… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…We identified the gene HanXRQChr14g0445121 located 1.4 Mb upstream of one of the markers. This product of this gene shared 47.71% of the sequence of the Arabidopsis protein RING-H2 FINGER PROTEIN ATL54, which is involved in the formation of the secondary cell wall (Noda et al, 2013). The second gene identified on chromosome 14 was HanXRQChr14g0459681, situated 20 kb upstream of the other marker.…”
Section: Resultsmentioning
confidence: 99%
“…We identified the gene HanXRQChr14g0445121 located 1.4 Mb upstream of one of the markers. This product of this gene shared 47.71% of the sequence of the Arabidopsis protein RING-H2 FINGER PROTEIN ATL54, which is involved in the formation of the secondary cell wall (Noda et al, 2013). The second gene identified on chromosome 14 was HanXRQChr14g0459681, situated 20 kb upstream of the other marker.…”
Section: Resultsmentioning
confidence: 99%
“…Borah and Khurana (2018) found that E3 ligase subunit F-box Kelch 1 (FBK1) was involved in root secondary cell wall thickening and lignin biosynthesis in rice. Another ubiquitin ligase protein, Arabidopsis Tóxicosen Levadura54 (ATL54) identified in Arabidopsis, participated in programmed cell death and secondary cell wall formation, although no significant variance on lignin content and composition in whole mature stem was observed by altering the expression level of ATL54 (Noda et al, 2013). TTNDFD associated marker MtChr4_32514187 was encompassed by a gene encoding sulfurtransferase (Str).…”
Section: Putative Candidate Genes With Functions Involved In Forage Qualitymentioning
confidence: 99%
“…The annealed doublestranded oligonucleotides were purified with a QIAquick Nucleotide Removal Kit (Qiagen). The electrophoresis of recombinant protein and probes, electroblotting, and probe detection were performed as described previously (Noda et al 2013b). …”
Section: Electrophoretic Mobility Shift Assay (Emsa)mentioning
confidence: 99%